Formation of a fringe: A look inside baleen morphology using a multimodal visual approach. (8th March 2023) - Vandenberg, Megan L.; Cohen, Karly E.; Rubin, Robert D.; Goldbogen, Jeremy A.; Summers, Adam P.; Paig‐Tran, E. W. Misty; Kahane‐Rapport, Shirel R.
Abstract: Filter‐feeding has been present for hundreds of millions of years, independently evolving in aquatic vertebrates' numerous times. Mysticete whales are a group of gigantic, marine filter‐feeders that are defined by their fringed baleen and are divided into two groups: balaenids and rorquals. Recent studies have shown that balaenids likely feed using a self‐cleaning, cross‐flow filtration mechanism where food particles are collected and then swept to the esophagus for swallowing. However, it is unclear how filtering is achieved in the rorquals (Balaenopteridae). Lunging rorqual whales engulf enormous masses of both prey and water; the prey is then separated from the water through baleen plates lining the length of their upper jaw and positioned perpendicular to flow. Rorqual baleen is composed of both major (larger) and minor (smaller) keratin plates containing embedded fringe that extends into the whale's mouth, forming a filtering fringe. We used a multimodal approach, including microcomputed tomography (µCT) and scanning electron microscopy (SEM), to visualize and describe the variability in baleen anatomy across five species of rorqual whales, spanning two orders of magnitude in body length. For most morphological measurements, larger whales exhibited hypoallometry relative to body length. µCT and SEM revealed that the major and minor plates break away from the mineralized fringes at variable distances from the gums. We proposed a model for estimating the effective pore size to determine whether flow scales with body length or prey size across species. We found that pore size is likely not a proxy for prey size but instead, may reflect changes in resistance through the filter that affect fluid flow. Abstract : The placement of baleen in a blue whale, with the baleen plates hanging down from the gums. Note the hairs that form the mat for filtration of prey from water. The illustration highlights the measurements taken, including the length of the plate, the thickness of the plate, the spacing between the plates and the diameter of the fringe. Illustration by California State University, Fullerton.